Epileptic Seizures and Right-Sided Hippocampal Swelling as Presenting Symptoms of Anti-IgLON5 Disease: A Case Report and Systematic Review of the Literature - Fu, Yaoqi; Zou, Xiangting; Liu, Ling (Frontiers in Neurology, 2022)
Background and Objective: Anti-IgLON5 disease is an uncommon neurological disorder characterized by diverse clinical manifestations. Although many relevant cases have been reported, our understanding of this disorder is still quite restricted. We present a rare case of anti-IgLON5 disease and performed a comprehensive systematic review of all published cases to expand the clinical spectrum of this disorder. Methods: We report a 61-year-old woman with an atypical presentation of epileptic seizures with abnormal signals in her right hippocampus on brain magnetic resonance imaging (MRI). A systematic review was performed of electronic databases, including PubMed, EMBASE, China National Knowledge Infrastructure (CNKI), WanFang and VIP China Science. Results: One hundred cases were identified from 61 publications. With heterogeneous clinical manifestations, we found that bulbar dysfunction, sleep apnea, gait instability and neurocognitive and behavioral symptoms are the most common symptoms of anti-IgLON5 disease. Anti-IgLON5 antibodies presented a higher positive rate and titer in the serum than in the cerebrospinal fluid (CSF). Haplotype DRB1∗10:01-DQB1∗05:01 is highly correlated with anti-IgLON5 disease. Only 27 patients have presented distinctive MRI alterations (39.7%). Approximately half of the cases are responsive to immunosuppressive or immunomodulatory treatment. Conclusion: Anti-IgLON5 disease is characterized by various clinical manifestations and laboratory findings. Immunotherapy may be effective in treating anti-IgLON5 disease, but the results are far from satisfactory. Studies with larger sample sizes are required to improve the current understanding of this disorder.